Den gode vilje og de vilde børn: Civiliseringens paradoks i den danske skole - Gilliam, Laura (Tidsskriftet Antropologi, 2010)
Laura Gilliam: The Good Will and the Wild Children. The Paradox of Civilizing in the Danish School Based on fieldwork in three Danish schools, this article focuses on the school’s project of transforming children into civilized citizens and the consequences this have for teachers’ work with children, and for children’s practices, social categories and construction of identity. It is argued that the civilizing project directed towards the groups regarded as the uncivilized of society: children, lower social classes and ethnic minorities, often results in these groups’ identification with uncivilized behavior. This paradox of civilizing is seen in the three classes, where an extensive focus on learning to be “social” and on adjusting all non-social behavior, make the teachers mark quite a few children as socially problematic, just like making trouble and other rejections of “civilised behaviour” become a relevant factor for the children’s social relationships in school, for their understanding of their own and other social categories and a relevant tool for their agency in school and relation to society. Due to the paradox of civilizing and the institutional logics of school, the children who reject the civilized ideal like this and come to identify against society, are often the gendered and ethnic categories, which the school is most eager to integrate and civilize. Keywords: Civilizing, the Danish school, opposition, ethnic minorities, institutional logics, identity.